Clinical efficacy maintains patients' positive attitudes toward fecal microbiota transplantation. Issue 30 (July 2016) - Xu, Lijuan; Zhang, Ting; Cui, Bota; He, Zhi; Xiang, Jie; Long, Chuyan; Peng, Zhaoyuan; Li, Pan; Huang, Guangming; Ji, Guozhong; Zhang, Faming
Abstract : Abstract: Few studies have been conducted on the attitudes of patients seeking fecal microbiota transplantation (FMT). This study aimed to investigate the reasons for patients with Crohn's disease (CD) seeking FMT and their attitude changes after FMT. In this prospective study, all included patients were diagnosed with CD for at least 6 months and intended to receive FMT. A questionnaire was designed to investigate the history of medical visits and patients' attitudes toward FMT. Only refractory patients who failed to clinically respond to previous treatment were selected for undergoing FMT. Three months after the first FMT, patients were required to complete the second questionnaire on attitudes toward the first FMT. A total of 207 patients with CD were included for questionnaire survey. In 118 refractory patients, 94.07% sought FMT because they had no other choice. In 89 nonrefractory patients, 78.65% sought FMT for the reason that they wanted to achieve better clinical results or even a cure, although the current treatment was effective for them. In all, 118 refractory patients received FMT. Three months after the first FMT, 88.98% (105/118) patients completed the questionnaire on patients' attitudes toward FMT. Of these 105 patients, 56.19% reported to have satisfactory clinical efficacy and 74.29% were willing to receive the second FMT. Moreover, 89.52% (94/105) showed their willingness to recommend FMT to other patients. In conclusion, this study at least first time demonstrated that patients with CD were willing to accept FMT due to its efficacy.